(untitled) (Research, Society and Development, 2025)
Puccinia cymbopogonis is an endophytic pathogen of lemongrass (Cymbopogon citratus), causing rust, a disease that leads to the development of pustules on the leaf surface, thereby reducing the commercial value of the leaves. Traditional control methods, such as the use of chemical pesticides, are not recommended for certain types of production, especially for tea intended for human consumption, making alternative strategies essential. Biological control emerges as a viable alternative, and the use of efficient microorganisms represents a feasible approach for identifying potential antagonists. This study aimed to isolate and morphologically analyze sixteen microorganisms with antagonistic activity against P. cymbopogonis, obtained from riparian forest areas in the Florestal region of Minas Gerais, Brazil. In vitro antagonism assays were performed using the Badalyan scale for assessing the antagonism index (AI) to select effective microorganisms. Five fungi exhibiting antagonistic activity in vitro were obtained and identified by morphological analysis as belonging to the genera Cladosporium spp. and Aspergillus spp. Three Cladosporium isolates exhibited an AI of 100% and were selected as promising candidates for subsequent in vivo testing.